Digital signal processor based over-current relay using fuzzy logic controller - Goh Y.L.; Ramasamy A.K.; Nagi F.H.; Abidin A.A.Z. (2023)
Protection and control are important aspects in real-time applications. Protection and control are required to ensure that safety and security of the system is achieved. In a power system, protection relays are used to minimize the disturbances caused by failure in the system to ensure continuous power delivery. Protection relays, such as over-current relays, are required to improve their reliability, since the power system is seriously affected by the faults either caused by internal or external sources. The relay must work efficiently to trip the circuit breakers if there are faults present. In this article, an over-current relay is designed based on fuzzy logic control to improve the overall performance of the relay. The over-current relay is implemented on a digital signal processor (TMS320F2812, Texas Instruments, Dallas, Texas, USA). The relay performance was compared with the IEC standard, and the results obtained are promising. Copyright Taylor & Francis Group, LLC.